2017
DOI: 10.1038/sigtrans.2017.66
|View full text |Cite
|
Sign up to set email alerts
|

Central role of myeloid MCPIP1 in protecting against LPS-induced inflammation and lung injury

Abstract: Although systemic inflammatory responses attributable to infection may lead to significant lung injury, the precise molecular mechanisms leading to lung damage are poorly understood and therapeutic options remain limited. Here, we show that myeloid monocyte chemotactic protein-inducible protein 1 (MCPIP1) plays a central role in protecting against LPS-induced inflammation and lung injury. Myeloid-specific MCPIP1 knockout mice developed spontaneous inflammatory syndromes, but at a late age compared to global MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 51 publications
5
59
1
Order By: Relevance
“…In turn, we showed that MCPIP1 negatively regulates adipogenesis by degrading transcripts coding for C/EBPβ [13,15]. Observations made by Li et al were similar to ours, demonstrating that transcripts coding for C/EBPβ and C/EBPδ are direct targets of MCPIP1 RNase [36].…”
Section: Discussionsupporting
confidence: 89%
“…In turn, we showed that MCPIP1 negatively regulates adipogenesis by degrading transcripts coding for C/EBPβ [13,15]. Observations made by Li et al were similar to ours, demonstrating that transcripts coding for C/EBPβ and C/EBPδ are direct targets of MCPIP1 RNase [36].…”
Section: Discussionsupporting
confidence: 89%
“…Malt1 also has proteolytic (aka paracaspase) activity. Malt1 paracaspase activity may enhance NF‐κB activation, directly or indirectly (stabilizing target gene mRNAs), by cleaving substrates including Bcl10, A20, Regnase‐1, Roquin‐1, or Roquin‐2; alternatively, Malt1 can antagonize canonical NF‐κB signaling by cleaving substrates including NF‐κBp65, MCPIP1, and HOIL1 . Malt1 also plays a role in the activation innate immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…During NFκB activation, MALT1 acts as an adaptor protein bridging CARD11 and BCL10 . However, MALT1 also has proteolytic activity and is known as “paracaspase.” Multiple MALT1 substrates have been identified; autoproteolysis and cleavage of BCL10, A20, Regnase‐1, Roquin‐1, and Roquin‐2 may enhance TCR‐mediated NFκB activation directly and indirectly, by stabilizing mRNAs of target genes, whereas cleavage of the NFκB subunit (p65), MCPIP1, and HOIL1 may inhibit canonical NFκB signaling . Thus, the effect of MALT1's paracaspase activity may complement or oppose its activity as a scaffolding protein.…”
Section: Introductionmentioning
confidence: 99%